AUTOBIOGRAPHY AND DEFACEMENT. GEORGES GUSDORF AND PAUL DE MAN - Tornero, Angélica (2021)
Since the last third of the twentieth century, we observe the propagation of Self-Writings. At the same time, more theorists and critics have revealed their interest in examining this type of writings. Generally speaking, we can identify two approaches: that of those who believe it is important to explore these writings in their ontological level and that of those who reject this angle, tending to opt for textual analysis. Georges Gusdorf’s and Paul de Man’s approaches represent these two attitudes. They encourage two distinct and contradictory concepts, especially, on the subject of autobiography. The aim of this article is to analyze from a comparative perspective Gusdorf’s and De Man’s assumptions, mainly those related to ontological and linguistic issues. It is in these two levels that we can clearly observe their dissents.